Prevalence of and factors associated with disclosure of experience of intimate partner violence among women in high migration communities in six southern African countries - Dim, Munachimso Vincentia (My University, 2021)
Background: Intimate Partner Violence (IPV) is a prevalent problem with devastating health consequences for women worldwide, yet many still fail to disclose their experience. Few studies address disclosure of experience of IPV among women in high migration communities. Thus, this study examines the prevalence of, and factors associated with disclosure of experience of intimate partner violence among women aged 15-49 years in high migration communities in six southern African countries. Methods: The study used data from the Sexual and Reproductive Health Rights-HIV Knows No Border Project's baseline survey. The baseline survey was conducted between May 2018 to June 2019. Data analysis was conducted using statistical software for data management and analysis (STATA) version 15. The prevalence of IPV and the disclosure of experience of IPV along with the factors associated with disclosure of experience of IPV were determined using descriptive statistics, univariable and multivariable logistic regression analysis at a 5% level of significance. A total of 1644 women were sampled for the analysis on the prevalence of experience of IPV while 514 women were used for the analysis on the prevalence of disclosure of experience of IPV. Results: Approximately one-third (514; 31%) of the women had experienced IPV in the past 12 months preceding the survey. Less than half (42%) of the women who were abused by their intimate partner disclosed their experience. Most women sought help from informal sources, especially their own families (52%). The odds of disclosure of experience of IPV were significantly higher among women that; experienced severe forms of violence (Adjusted Odds Ratio (AOR)) =2.46, 95% CI: 1.47; 4.13); sustained injuries due to IPV (AOR=2.92, 95% CI: 1.74; 4.88); witnessed inter-parental violence (AOR=0.57, 95% CI: 0.35; 0.92); had a partner with controlling behaviour(s) (AOR=3.05, 95% CI: 1.10, 8.48) and being in an older age group (AOR=1.8, 95% CI: 1.01, 3.23). Conclusion: Despite the high prevalence of IPV, majority of the women were silent about their experience of abuse. The factors associated with disclosure of experience of IPV were the age of the women, the severity of violence, history of inter-parental violence, controlling behaviour ii of their partner and having sustained injury as a result of IPV. Thus, strategies must be put in place to encourage disclosure, particularly to formal sources and to eliminate violence against women in society in all its forms. Future research should explore why women are not disclosing their experiences of IPV, specifically in high migration communities.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology (Biostatistics) to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2021